DEVELOPMENT OF A NUMERACY LITERACY TEST INSTRUMENT BASED ON THE ANDROID ISPRING SUITE FOR GRADE VIII JUNIOR HIGH SCHOOL STUDENTS - Elwan Stiadi; Yusnia Yusnia; Nader U sin (Department of Mathematics Education Universitas Borneo Tarakan, 2025)
The rapid development of technology and communication has penetrated the field of education, including in the development of evaluation instruments. Android-based test instruments have been widely studied and proven to have a positive impact on the learning process. This study aims to develop an Android-based numeracy literacy test instrument using iSpring Suite for Grade VIII junior high school students. This research focused on 30 students in Class VIII B at SMP Negeri 6 Bengkulu City. The results of the development are expected to produce a test instrument that is valid, reliable, practical, and has good item quality. This study employs the ADDIE development model which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The Analysis stage was conducted to identify the needs of the test instrument, while the Design stage involved the design of an Android-based instrument. At the Development stage, validation was carried out by expert validators using a 4-point Likert scale, which includes the validity of the material, construction, language, and media. The developed product prototype was demonstrated through video documentation, while the application was distributed as an APK file for field testing and user feedback collection. Implementation data was analyzed using the SPSS program to evaluate the reliability and practicality of the instrument. Expert validation yielded an average validity score of 3.82 (Aiken’s V = 0.94, very valid category), with a reliability coefficient of r₁₁ = 0.890 (high reliability). The practicality test results from students showed a score of 85.2% (very practical category). The results of the study showed that the developed test instrument met the criteria for validity, reliability, and practicality. In addition, the test items have a balanced level of difficulty (2 medium, 2 difficult), good discriminating power (D range: 0.333–0.467), and optimally functioning distractors. This instrument contributes to the development of digital-based evaluation media to improve the quality of numeracy literacy learning aligned with Kurikulum Merdeka and AKM frameworks. Keywords: Android, ISpring Suite, Numeracy Literacy, Test Instrument. Perkembangan teknologi dan komunikasi yang pesat telah merambah bidang pendidikan, termasuk dalam pengembangan instrumen evaluasi. Instrumen tes berbasis Android telah banyak dipelajari dan terbukti memiliki dampak positif pada proses pembelajaran. Penelitian ini bertujuan untuk mengembangkan instrumen tes literasi numerasi berbasis Android menggunakan iSpring Suite untuk siswa kelas VIII SMP. Penelitian ini berfokus pada 30 siswa kelas VIII B di SMP Negeri 6 Kota Bengkulu. Hasil pengembangan diharapkan menghasilkan instrumen tes yang valid, reliabel, praktis, dan memiliki kualitas item yang baik. Penelitian ini menggunakan model pengembangan ADDIE yang mencakup lima tahapan: Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi. Tahap Analisis dilakukan untuk mengidentifikasi kebutuhan instrumen tes, sedangkan tahap Desain melibatkan desain instrumen berbasis Android. Pada tahap Pengembangan, validasi dilakukan oleh validator ahli menggunakan skala Likert 4 poin, yang meliputi validitas materi, konstruksi, bahasa, dan media. Prototipe produk yang dikembangkan didemonstrasikan melalui dokumentasi video, sedangkan aplikasi didistribusikan sebagai file APK untuk pengujian lapangan dan pengumpulan umpan balik pengguna. Data implementasi dianalisis menggunakan program SPSS untuk mengevaluasi reliabilitas dan kepraktisan instrumen. Validasi ahli menghasilkan skor validitas rata-rata 3,82 (Aiken’s V = 0,94, kategori sangat valid), dengan koefisien reliabilitas r₁₁ = 0,890 (reliabilitas tinggi). Hasil uji kepraktisan dari siswa menunjukkan skor 85,2% (kategori sangat praktis). Hasil penelitian menunjukkan bahwa instrumen tes yang dikembangkan memenuhi kriteria validitas, reliabilitas, dan kepraktisan. Selain itu, item tes memiliki tingkat kesulitan yang seimbang (2 sedang, 2 sulit), daya diskriminasi yang baik (rentang D: 0,333–0,467), dan distraktor yang berfungsi optimal. Instrumen ini berkontribusi pada pengembangan media evaluasi berbasis digital untuk meningkatkan kualitas pembelajaran literasi numerik yang selaras dengan kerangka kerja Kurikulum Merdeka dan AKM. Kata kunci: Android, Instrumen Tes, ISpring Suite, Literasi Numerasi